Smartphone use as a possible risk factor for myopia - Mccrann, Saoirse; Loughman, James; Butler, John S; Paudel, Nabin; Flitcroft, Daniel Ian (Clinical and experimental optometry, 2021)
This study demonstrates an association between myopia and smartphone data usage. Youths now spend more time participating in near tasks as a result of smartphone usage. This poses an additional risk factor for myopia development/progression and is an important research question in relation to potential myopia management strategies. Children are now exposed to another possible environmental risk factor for myopia - smartphones. This study investigates the amount of time students spend on their smartphones and their patterns of smartphone usage from a myopia perspective. Primary, secondary and tertiary level students completed a questionnaire exploring patterns of smartphone usage and assessing their attitudes toward potential myopia risk factors. Device-recorded data usage over an extended period was quantified as the primary and objective indicator of phone use. Average daily time spent using a smartphone was also quantified by self-reported estimates. Refractive status was verified by an optometrist. Smartphone ownership among the 418 students invited to participate was over 99-per cent. Average daily smartphone data and time usage was 800.37 ± 1,299.88-MB and 265.16 ± 168.02-minutes respectively. Myopic students used almost double the amount of smartphone data at 1,130.71 ± 1,748.14-MB per day compared to non-myopes at 613.63 ± 902.15-MB (p = 0.001). Smartphone time usage was not significantly different (p = 0.09, 12-per cent higher among myopes). Multinomial logistic regression revealed that myopic refractive error was statistically significantly associated with increasing daily smartphone data usage (odds ratio 1.08, 95% CI 1.03-1.14) as well as increasing age (odds ratio 1.09, 95% CI 1.02-1.17) and number of myopic parents (odds ratio 1.55, 95% CI 1.06-2.3). Seventy-three per cent of students believed that digital technology may adversely affect their eyes. This study demonstrates an association between myopia and smartphone data usage. Given the serious nature of the ocular health risks associated with myopia, our findings indicate that this relationship merits more detailed investigation.